2017
DOI: 10.1590/0101-60830000000122
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related quality of life related to mental health and sociodemographic indicators in adolescents

Abstract: Background: A total of 6150 junior and senior high school students aged 11-18 years participated in this study. Their level of pain-related QOL was assessed using the pain subscale of the Taiwanese QOL Questionnaire for Adolescents. The severities of depression, suicidality, anxiety, and alcohol abuse were also examined. Objectives: This study examined the associations between pain-related quality of life (QOL) and sociodemographic characteristics and those between pain-related QOL and mental health problems s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The majority of selected studies had been published in the last decade (n=20 33,34,36,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ; 80% published after 2010; table 1). Studies were geographically diverse, and mainly based on community samples (n=17 [33][34][35][36]43,44,[46][47][48][49][50][51]53,55,[57][58][59] ), using cross-sectional designs (n=18 35,41,43,46,47,[49][50][51][52][53][54][55][56]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of selected studies had been published in the last decade (n=20 33,34,36,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ; 80% published after 2010; table 1). Studies were geographically diverse, and mainly based on community samples (n=17 [33][34][35][36]43,44,[46][47][48][49][50][51]53,55,[57][58][59] ), using cross-sectional designs (n=18 35,41,43,46,47,[49][50][51][52][53][54][55][56]…”
Section: Resultsmentioning
confidence: 99%
“…Studies were geographically diverse, and mainly based on community samples (n=17 [33][34][35][36]43,44,[46][47][48][49][50][51]53,55,[57][58][59] ), using cross-sectional designs (n=18 35,41,43,46,47,[49][50][51][52][53][54][55][56][57][58][59][60][61] ). Eighteen studies recruited participants aged 10 to 19 years, [33][34][35][36]42,[45][46][47][48][50][51][52][53][57][58][59]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 However, research found that boys with sexual minority or gender nonconformity have a higher risk to encounter negative criticism and a lower level of subjective school safety than girls with sexual minority or gender nonconformity. 52 Moreover, girls have higher levels of depression, 53 anxiety, 54 and pain 12 compared with boys. Thus the present study focused on gay and bisexual men.…”
Section: Discussionmentioning
confidence: 99%
“… 11 According to our review of relevant literature, no study has evaluated the relationship between homophobic bullying victimization and physical pain in early adulthood among gay and bisexual men. Because both anxiety and physical pain can affect youths’ mental health and quality of life, 12 , 13 the effects of homophobic bullying victimization in childhood on anxiety and physical pain in early adulthood among gay and bisexual men warrant further research.…”
Section: Introductionmentioning
confidence: 99%